The new net zero : leading-edge design and construction of homes and buildings for a renewable energy future - Maclay, William, 1948- (White River Junction, Vermont : Chelsea Green Publishing, 2014)
'The new threshold for green building is not just low energy, it's net-zero energy. In The New Net Zero, sustainable architect Bill Maclay charts the path for designers and builders interested in exploring green design's new frontier net-zero-energy structures that produce as much energy as they consume and are carbon neutral; In a nation where traditional buildings use roughly 40 percent of the total fossil energy, the interest in net-zero building is growing enormously-among both designers interested in addressing climate change and consumers interested in energy efficiency and long-term savings. Maclay, an award-winning net-zero designer whose buildings have achieved high-performance goals at affordable costs, makes the case for a net-zero future; explains net-zero building metrics, integrated design practices, and renewable energy options; and shares his lessons learned on net-zero teambuilding;Designers and builders will find a wealth of state-of-the-art information on such considerations as air, water, and vapor barriers; embodied energy; residential and commercial net-zero standards; monitoring and commissioning; insulation options; costs; and more;The comprehensive overview is accompanied by several case studies, which include institutional buildings, commercial projects, and residences. Both new-building and renovation projects are covered in detail;The New Net Zero is geared toward professionals exploring net-zero design, but also suitable for nonprofessionals seeking ideas and strategies on net-zero options that are beautiful and renewably powered'--
Includes bibliographical references and index.
Keywords: Sustainable buildings; Sustainable construction; Sustainable architecture; Architecture and climate